Assessment of Potential Benefits of Functional Food Characteristics of Beetroot Energy Drink and Flavored Milk. (15th March 2022) - Ashraf, Seema; Sayeed, Syed Asad; Ali, Rashida; Vohra, Fahim; Ahmed, Naseer; Alam, Mohammad Khursheed
Abstract : Objective . This study was designed to determine the antioxidant activity of the extracts of beetroot by using beetroot energy drink and flavored milk (products). Material & Methods . This experimental trial was conducted at Jinnah University for Women, Pakistan, under the approval of local institutional review board number JUW/DFST/RCB010/2020. All the materials such as beetroot, carrot, cucumber, and lemon were obtained commercially from which two products were formulated: beetroot energy drink (sample1) and flavored milk (sample 2). These formulated products were evaluated for quality analysis (pH and brix), phytochemical screening using the Keller-Kiliani test, Salkowski's test, Alkaline reagent test, lead acetate test, ferric chloride test, protein test, quantitative test of phenol, antioxidant activity, sensory analysis, and shelf life study. The paired t -test was applied to detect significant differences between two samples. Results . The phytochemical analysis revealed that cardiac glycosides, phytosterol, flavonoids, and terpenoids were found in both energy booster drink (EBD) and flavored milk (FM) except phenolic compounds that were found only in EBD. The antioxidant capacity of beetroot juice was far greater than FM. The statistical sensorial analysis of FM and EBD reported a significant mean difference between most of the groups with p < 0.0001 . Conclusion . This study concludes that energy drinks having beetroot indicated higher antioxidant capacity than flavored milk. The nutraceutical products (energy booster drink and flavored milk) containing beetroot are enriched with optimum quantities of proteins and fats and low carbohydrates at a stable pH with an adequate total energy content.